ABOUT THE POSSIBILITY TO REDUCE HYDRAULIC LOSSES IN THE CONTROL SYSTEM OF HYDRAULIC DRIVE WITH VARIABLE–DISPLACEMENT PUMP - Burennikov, Yuriyy; Kozlov, Leonid; Repinskyy, Serhiy (Scientific Works of Vinnytsia National Technical University, 2011)
The paper presents the mathematical model of the automatic regulator for a variable-displacement pump. This regulator provides hybrid control means combining both pump flow rate stabilization and fixed-power mode of pump operation. There had been determined the hydraulic power losses in the suggested system. The possibilities of their reduction have been analyzed in order to eliminate high power losses in the hydraulic drive.